Electronic component mounting substrate and electronic apparatus

By using a characteristic anti-peel layer on the electronic parts mounted substrate, the problem of easy peeling of parts caused by miniaturization and thinning is solved, the reliability and wear resistance in high temperature and high humidity environments are improved, and the stability of electronic parts is achieved Sex and long-term use.

CN119325744AActive Publication Date: 2025-01-17아티엔스가부시키가이샤 +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202480002751.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-11-30
Filing Date
2024-03-27
Publication Date
2025-01-17
Estimated Expiration
2044-03-27

AI Technical Summary

Technical Problem

During the process of miniaturization and thinning of existing electronic parts, the adhesion between the electronic parts and the substrate is reduced, resulting in the parts being easily peeled off, and it is difficult to use for a long time in high temperature and high humidity environments, and the friction and damage resistance are insufficient.

Method used

The anti-flaking layer with a specific static friction coefficient change rate and an index is used to form an anti-flaking layer with a thickness of 5 μm to 300 μm by combining adhesive and filler. The anti-flaking sheet is produced by stamping forming and other methods, and the anti-flaking sheet is heated and pressurized. It is made in close contact with the electronic parts and the substrate to form a protective layer that is resistant to wear and damage.

Benefits of technology

Effectively prevent electronic parts from falling off under external damage and high temperature and humidity environments, improve the reliability and wear resistance of parts, and ensure the long-term stability of electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119325744A_ABST
    Figure CN119325744A_ABST
Patent Text Reader

Abstract

Provided is an electronic component mounting substrate which is provided with an anti-peeling layer that has excellent adhesion and scratch resistance and increases the smoothness of the corners of the component after processing, and which firmly covers the substrate and the electronic component on the substrate. Therefore, in the step of carrying the electronic component, the hooking between the nail of a person or other components and the carried electronic component is inhibited, and the electronic component is prevented from peeling off from the substrate due to external damage. This electronic component mounting substrate is provided with a substrate, an electronic component, and an anti-peeling layer. The anti-peeling layer satisfies the following conditions: (1) the rate of change (X) of the static friction coefficient as determined by the following [formula 1] is-50% to 200%, inclusive, and (2) the index (Y) as determined by the following [formula 2] is 0.8 to 20.0, inclusive. [Formula 1] X = ([mu] k300-[ mu] k100) / [mu] k100 * 100 [Formula 2] Y = R2 / (R1 + A1).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an electronic component mounting substrate and an electronic device. Background Art

[0002] Since terminal electronic devices represented by smartphones and wearable devices are used in a variety of environments, high reliability is required to prevent malfunctions even under harsh conditions. Furthermore, by promoting the miniaturization and thinning of electronic devices, the size of the electronic component mounting substrate used is also miniaturized, and the grounding area between the substrate and the electronic components is also reduced. As a result, the adhesion between the electronic components and the substrate is reduced, and the possibility of the electronic components peeling off from the substrate increases. Therefore, in terms of physical damage, heat and humidity, the necessity of preventing the electronic components from being damaged or slipping increases.

[0003] Therefore, there is known a method of protecting electronic components from external damage by filling electronic components such as integrated circuit (IC) chips and multilayer ceramic capacitors (MLCC) with a resin layer (Patent Document 1).

[0004] However, from the viewpoint of thinning of electronic component mounting substrates and cost reduction, it is required to form a protective layer thinner and to suppress the thickness after processing.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2021-004314 Summary of the invention

[0008] Problems to be solved by the invention

[0009] As described above, the invention related to the electronic component mounting substrate protected by coating is disclosed. However, if the protective layer is thinned, many problems described below may occur. Therefore, an electronic component mounting substrate that can solve these problems at one go is desired.

[0010] The steps of assembling electronic devices include several steps of mounting various electronic components on a substrate using solder or adhesive. After the electronic component mounting substrate is manufactured, it undergoes steps such as assembly to the electronic device or reliability testing. However, during this operation, sometimes the electronic components may be caught by human nails or other components and fall off the substrate or shift in position. In recent years, the miniaturization and thinning of electronic components represented by multilayer ceramic capacitors (hereinafter referred to as MLCC) have been rapidly promoted, and the grounding area with the substrate has also become smaller, thereby reducing the adhesion between the components and the substrate, and the importance of preventing the electronic components from falling off has further increased.

[0011] In addition, a protective member with abrasion resistance or damage resistance is required to withstand the situation even when a hard member such as metal contacts or rubs against the electronic component. Furthermore, a highly reliable electronic component mounting substrate is required in which the protective member will not peel off even if used for a long time in a high temperature and high humidity environment.

[0012] The present disclosure aims to provide a highly reliable electronic component mounting substrate which has excellent wear resistance and scratch resistance even in a miniaturized and thinned electronic component mounting substrate, in which electronic components are unlikely to fall off due to external damage and which can be used for a long period of time under high temperature and high humidity.

[0013] Means of solving the problem

[0014] The present inventors and others have made great efforts to study and found that the above-mentioned problem can be solved by using an article (electronic component mounting substrate, anti-peeling layer and anti-peeling sheet) having the following characteristics, thereby completing the present disclosure. That is, the present disclosure is about an electronic component mounting substrate, anti-peeling layer and anti-peeling sheet characterized by the following contents.

[0015] [1]: A substrate for mounting electronic components, characterized in that it comprises: a substrate; an electronic component mounted on at least one surface of the substrate; and an anti-peeling layer for covering the substrate and the electronic component, wherein the anti-peeling layer satisfies all of the following (1) and (2).

[0016] (1) The rate of change X of the static friction coefficient obtained by the following [Formula 1] is not less than -50% and not more than 200%.

[0017] X=(μk 300 -μk 100 ) / μk 100 ×100[Formula 1]

[0018] (μk 100 ; The static friction coefficient of the anti-stripping layer at the 100th reciprocating wear test, μk 300; The static friction coefficient of the anti-stripping layer during the 300th reciprocating wear test)

[0019] (2) The index Y obtained by the following [Formula 2] is 0.8 or more and 20.0 or less.

[0020] Y=R2 / (R1+A1)[Formula 2]

[0021] (R1: the curvature radius of the curved surface at the corner of the electronic component in the cross section of the electronic component mounting substrate, R2: the curvature radius of the corner of the anti-peeling layer in the cross section of the electronic component mounting substrate, A1: the thickness of the corner of the anti-peeling layer in the cross section of the electronic component mounting substrate)

[0022] [2]: The electronic component mounting substrate according to [1], wherein the anti-peeling layer comprises a binder (A) and a filler (B),

[0023] The BET (Brunauer-Emmett-Teller) specific surface area of ​​the filler (B) [m 2 The product of the content [mass %] of the filler (B) in 100 mass % of the spalling prevention layer is 0.01 [mass %·m 2 / g]~15[mass %·m 2 / g].

[0024] [3]: The electronic component mounting substrate according to [1] or [2], wherein the thickness A2 of the peeling prevention layer is 5 μm to 300 μm.

[0025] [4]: An electronic device equipped with the electronic component mounting substrate described in any one of [1] to [3].

[0026] Effects of the Invention

[0027] According to the present disclosure, it is possible to provide an electronic component mounting substrate that can suppress the detachment of electronic components due to external damage for a long period of time even in a miniaturized and thin electronic component mounting substrate, and an electronic device having the electronic component mounting substrate mounted thereon. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] [ Figure 1 ] is a schematic cross-sectional view of the electronic component mounting substrate of the present embodiment.

[0029] [ Figure 2 ] is a schematic cross-sectional view of the electronic component mounting substrate of the present embodiment, showing R1, R2, and A1 on the corner curved surface of the electronic component constituting the index Y.

[0030] [ Figure 3] is a diagram showing a partial flow of manufacturing steps for an electronic component mounting substrate according to the present embodiment.

[0031] [ Figure 4 ] is a schematic cross-sectional view showing an example of an electronic component mounting substrate according to the present embodiment.

[0032] [ Figure 5 ] is a diagram showing an evaluation method for an electronic component mounting substrate according to an embodiment. DETAILED DESCRIPTION

[0033] The content of the present disclosure will be described below by way of the embodiments of the invention, but the following embodiments do not limit the inventions involved in the claims. In addition, not all combinations of features described in the embodiments are essential to the solutions provided by the invention.

[0034] 《Substrates for mounting electronic components》

[0035] like Figure 1 As shown, the electronic component mounting substrate 10 of the present disclosure includes a substrate 1, an electronic component 2 mounted on the substrate 1, and an anti-peeling layer 3 for covering and protecting the substrate 1 and the electronic component 2. The substrate 1 or the electronic component 2 has a region (not shown) containing a resin component, and the anti-peeling layer 3 covers the surface thereof.

[0036] The substrate 1 can be selected arbitrarily as long as it can carry the electronic components 2 and can withstand the molding process of various uses. Electrodes / wiring patterns, through holes (not shown), etc. can be arbitrarily set on the substrate 1. The substrate 1 can be a rigid substrate or a flexible substrate. As the substrate 1, for example, there can be listed: a working board with a conductive pattern composed of copper foil, etc. formed on the surface and / or inside, a mounting module substrate, a printed wiring board, and a combined substrate formed by a combination method, etc.

[0037] The electronic component 2 includes, for example, a connector, a film capacitor, a component molded from a wafer or a wire, an inductor, a thermistor, an MLCC, a coil, a diode, an electrolytic capacitor, a quartz oscillator, etc. Among these, MLCC and IC chips are preferably used as the electronic component 2 in the present disclosure because of the advancement of miniaturization.

[0038] When a plurality of electronic components 2 are mounted, the shapes and heights of the electronic components 2 may be the same or different.

[0039] The size or height of the electronic component 2 is not particularly limited, but in the context of recent miniaturization and thinning, the height is preferably less than 3 mm. The shape of the IC chip can be cylindrical, coin-shaped, thin-film-shaped, etc. in addition to a rectangular shape. MLCC is preferably 0402 (length 0.4 mm, width 0.2 mm) and 0603 (length 0.6 mm, width 0.3 mm) as the mainstream package size, but other large parts such as 1005 or 1608 can also be carried. The shape of the inductor includes a solenoid, a dome-shaped coil, a flat coil, etc. Thermistors include rectangular or cylindrical, pin-shaped, etc. for surface mounting.

[0040] The electronic component 2 can be electrically connected to the substrate via the solder bump 4, or the substrate can be directly connected to the connection terminal extending from the electronic component. Figure 1 As shown, a hollow portion 5 is generated between the electronic component 2 and the substrate 1 .

[0041] The anti-peeling layer 3 may cover and protect the electronic component 2 and the substrate 1 in a manner of maintaining the hollow portion 5 , or may cover and protect the electronic component 2 and the substrate 1 in a manner of filling the hollow portion 5 .

[0042] The peeling prevention layer 3 can be produced by the method described later.

[0043] The anti-peeling layer 3 covers the substrate 1 and the electronic component 2. Figure 1 In the embodiment, the substrate 1 is coated from the upper surface of the electronic component 2 to the side surface, and then the entire surface or a part of the end surface of the substrate 1 is coated. That is, a coating layer (anti-stripping layer 3) is provided to cover the step difference portion (concave-convex portion) formed by mounting the electronic component 2. The anti-stripping layer 3 uses an anti-stripping sheet ( Figure 3 The method of forming the anti-stripping layer 3 by the anti-stripping sheet 6 is not limited, but preferably any one of a stamping method, a three-dimensional surface coating method (three-dimensional overlay method (TOM)), a vacuum forming method, a pressure forming method, a vacuum pressure forming method, and an injection molding method. Among these, the most preferred method for forming the anti-stripping layer 3 by the anti-stripping sheet 6 is a stamping method.

[0044] exist Figure 1 In the example of mounting electronic components 2 on one surface of the substrate 1, the electronic components 2 may be mounted on both surfaces of the substrate 1 and the both surfaces of the substrate 1 may be covered by the anti-peeling layer 3. As described above, in the electronic component mounting substrate of the present disclosure, it is sufficient as long as the electronic components 2 are mounted on at least one surface of the substrate 1 and the anti-peeling layer 3 covering the substrate 1 and the electronic components 2 is provided.

[0045] Anti-stripping layer

[0046] Next, the peeling prevention layer in the present disclosure will be described in more detail. The peeling prevention layer 3 is used to prevent the two sets of electronic components arranged on the substrate 1 as described above from peeling off from the mounting substrate 1 .

[0047] The peeling prevention layer 3 satisfies all of the following (1) and (2).

[0048] (1) The rate of change X of the static friction coefficient obtained by the following [Formula 1] is not less than -50% and not more than 200%.

[0049] (2) The index Y obtained by the following [Formula 2] is 0.8 or more and 20.0 or less.

[0050] In addition, these numerical values ​​X and numerical values ​​Y are values ​​calculated by [Formula 1] and [Formula 2] shown below, and the measurement of X and Y is based on the method and conditions described in the Examples described later.

[0051] 《Rate of change of static friction coefficient X》

[0052] The change rate X of the static friction coefficient obtained by the reciprocating wear test of the spalling prevention layer (hereinafter referred to as the change rate X of the static friction coefficient) can be expressed by the following [Formula 1].

[0053] X=(μk 300 -μk 100 ) / μk 100 ×100[Formula 1]

[0054] Here, μk 100 is the static friction coefficient of the anti-stripping layer at the 100th reciprocating wear test, μk 300 It is the static friction coefficient of the anti-spalling layer at the 300th reciprocating wear test.

[0055] Regarding the static friction coefficient μk 100 , static friction coefficient μk 300 The determination method is described in detail in the examples.

[0056] The rate of change X of the static friction coefficient was tested using a wear tester. The number of times the static friction coefficient stabilized during measurement was compared with the number of times used as a reference for judging whether or not wear resistance existed. Therefore, the 100th static friction coefficient μk was used. 100 The 300th static friction coefficient μk, which is an indicator of wear resistance 300Calculate. The rate of change X of the static friction coefficient becomes an indicator for confirming that a certain static friction coefficient is maintained when the reciprocating wear test is continued, that is, the wear resistance. In addition, the positive rate of change X of the static friction coefficient indicates the progress of wear, and the larger the value, the lower the wear resistance. The negative case indicates that the progress of wear is small, and the sliding on the surface of the anti-stripping layer increases, which is considered to be affected by the filler exposed when the film surface is cut or the wear powder and friction heat on the surface of the anti-stripping layer.

[0057] Furthermore, from the perspective of obtaining stable measured values, the test using the wear tester is performed on the smooth surface of the anti-peeling layer formed on the resin-containing area of ​​the electronic component or substrate. The so-called resin area refers to the part of the surface covered with resin such as molded resin or glass epoxy resin.

[0058] By setting the change rate X of the static friction coefficient in the present disclosure to be between -50% and 200%, the wear resistance of the anti-peeling layer on the electronic component mounting substrate can be optimized. X is preferably between -25% and 150%, more preferably between -5% and 100%. By setting the change rate X on the anti-peeling layer to the above range, the anti-peeling layer is not easily scratched, and the wear resistance and damage resistance are improved.

[0059] [Control Method]

[0060] The method for controlling the rate of change X of the static friction coefficient of the anti-peeling layer can be applied to all methods including previously known methods. For example, the following methods can be cited: a method for hardening the surface of the anti-peeling layer by adjusting the ingredients added to the anti-peeling layer to improve the resistance to friction, a method for improving the smoothness of the oil replenishing surface by adding wax components, etc., a method for reducing the surface concave-convex by reducing the added granular components or changing the shape (reduction of the surface friction coefficient), a method for improving the heat resistance of the anti-peeling layer, and a method for reducing the surface concave-convex according to the type of protective film used when forming an anti-peeling sheet as a precursor of the anti-peeling layer on an electronic component mounting substrate. As a method for controlling the wear resistance of the surface of the anti-peeling layer, it is not limited to the exemplified method, but as long as it is a method for increasing the amount of hardener in the anti-peeling layer to harden the surface, or a method for adjusting the amount and shape of the granular material in the anti-peeling layer to reduce the surface concave-convex, there is no need to perform special pretreatment / post-treatment, so it is preferred from the perspective of productivity.

[0061] Index Y

[0062] The peeling prevention layer in the present disclosure has an index Y calculated from the following [Formula 2] of 0.8 or more and 20.0 or less. By setting the numerical range as described above, a suitable shape that smoothly covers the surface of the electronic component mounting substrate and prevents peeling of the electronic component can be obtained.

[0063] From the viewpoint of ensuring uniformity of the thickness of the peeling prevention layer (followability to components) or thickness at the corners of electronic components, Y is preferably 0.9 or more and 12.0, and more preferably 1.0 or more and 5.0 or less.

[0064] Y=R2 / (R1+A1)[Formula 2]

[0065] Furthermore, R2, R1, and A1 in [Formula 2] are obtained by Figure 2 The measured values ​​of the cross section of the electronic component mounting substrate 11 shown when the cross section is taken perpendicularly to the substrate surface are calculated, and the curvature radius of the curved surface at the corner of the electronic component 2 in the cross section of the electronic component mounting substrate 11 is set to R1, the curvature radius of the corner of the anti-peeling layer 3 in the cross section of the electronic component mounting substrate 11 mounted thereon is set to R2, and the corner thickness of the anti-peeling layer 3 in the cross section of the electronic component mounting substrate 11 is set to A1 (hereinafter referred to as the corner thickness A1 of the anti-peeling layer).

[0066] The cross section of the electronic component mounting substrate 11 can be cut by dicing or polishing, and R2, R1, and A1 can be obtained by length measurement of the cross section using, for example, a digital microscope VHX-7000 (manufactured by KEYENCE Corporation).

[0067] Note that the curvature radius R1 and the curvature radius R2 indicate the locations where snagging is most likely to occur at each corner, and therefore refer to the curvature radius that is the minimum value when measuring at each corner.

[0068] Index Y is a value representing the change in smoothness between the corners of the electronic component 2 and the corners of the anti-peeling layer 3 on the electronic component. By setting the index Y to the above range, it is possible to prevent the electronic component 2 from peeling off due to the electronic component 2 being caught by nails or other parts during the inspection of the electronic component mounting substrate 11 or when the electronic component mounting substrate 11 is mounted on an electronic device in a subsequent step.

[0069] The index Y can be controlled by adjusting the followability and fluidity of the anti-stripping sheet 6 to the electronic component 2 during processing. Specifically, the following methods can be cited: adjusting by selecting the adhesive (A) and filler (B) constituting the anti-stripping sheet 6 described later, adjusting the followability of the anti-stripping sheet 6 to the substrate 1 and the electronic component 2 by adjusting the processing conditions (processing temperature, processing time, pressurization conditions, vacuum degree, etc.) during the processing of the anti-stripping sheet 6, and controlling the fluidity of the anti-stripping sheet 6 by changing the laminated structure during the processing of the anti-stripping sheet 6. When a plurality of anti-stripping sheets 6 are used, different methods can be applied to each of them, or a common method can be applied.

[0070] 《Adhesive (A)》

[0071] The anti-stripping layer 3 contains a binder (A). The binder (A) becomes the matrix of the anti-stripping layer and has the function of carrying the filler (B) or other optional components described later. The binder (A) can be a thermoplastic resin, or any one of a thermosetting resin and a curable compound.

[0072] [Thermoplastic resin]

[0073] Examples of the thermoplastic resin include polyolefin resins, vinyl resins, styrene-acrylic resins, diene resins, terpene resins, petroleum resins, cellulose resins, polyamide resins, polyurethane resins, polyester resins, polycarbonate resins, polyimide resins, liquid crystal polymers, fluororesins, etc. The thermoplastic resins are not particularly limited, but from the viewpoint of heat resistance, polyamide resins, polyurethane resins, polyester resins, polycarbonate resins, polyimide resins, liquid crystal polymers, and fluororesins are more preferred.

[0074] The thermoplastic resins may be used alone or in combination of two or more.

[0075] [Thermosetting resin]

[0076] Thermosetting resins are resins having multiple functional groups that can react with curable compounds. Examples of the functional groups include: hydroxyl, phenolic hydroxyl, anhydride, methoxymethyl, carboxyl, amino, epoxy, oxetane, oxazoline, oxazine, aziridine, thiol, isocyanate, blocked isocyanate, blocked carboxyl, silanol, etc. Examples of thermosetting resins include: acrylic resins, maleic acid resins, polybutadiene resins, polyester resins, polyurethane resins, polyurethane urea resins, epoxy resins, oxetane resins, phenoxy resins, polyimide resins, polyamide resins, polyamideimide resins, phenolic resins, alkyd resins, amino resins, polylactic acid resins, oxazoline resins, benzoxazine resins, silicone resins, fluororesins and other known resins.

[0077] The thermosetting resins may be used alone or in combination of two or more.

[0078] Among these, in terms of heat resistance, preferred thermosetting resins are polyurethane resins, polyurethane urea resins, polyester resins, epoxy resins, phenoxy resins, polyimide resins, polyamide resins, and polyamideimide resins.

[0079] [Hardening compound]

[0080] The curable compound has a plurality of functional groups that can react with the functional groups of the thermosetting resin. Examples of the curable compound include known compounds such as epoxy compounds, acid anhydride group-containing compounds, isocyanate compounds, aziridine compounds, amine compounds, phenol compounds, and organometallic compounds.

[0081] The curable compounds may be used alone or in combination of two or more.

[0082] The curable compound is preferably difunctional or higher, and more preferably trifunctional or higher. From the viewpoint of adjusting the crosslinking density to achieve both processing suitability during molding of the electronic component mounting substrate described later and temporal stability of the composition as a precursor of the anti-stripping sheet, it is desirable to use a difunctional curable compound and a trifunctional or higher curable compound in combination.

[0083] By adjusting the content of the curable compound as described below, a strong cross-linking structure is formed on the anti-stripping layer, and the adhesion between the anti-stripping layer and the substrate is improved, thereby improving reliability. In this way, the adhesion between the anti-stripping layer and the substrate can also be adjusted by the content of the curable compound in the composition.

[0084] Relative to 100 parts by mass of the thermosetting resin, the various bifunctional curable compounds preferably contain 1 to 50 parts by mass, and more preferably contain 15 to 30 parts by mass. By making the amount of the bifunctional curable compound more than 1 part by mass, a stronger cross-linked structure is formed on the anti-stripping layer, thereby further improving the resistance to thermal damage. Furthermore, by making the amount of the bifunctional curable compound more than 15 parts by mass, the hardness or strength of the surface of the anti-stripping layer can be adjusted, thereby further improving the wear resistance. On the other hand, by making the amount of the curable compound less than 50 parts by mass, it is easy to suppress the excessive hardening of the anti-stripping layer, thereby easily suppressing the cracking caused by the shrinkage of the anti-stripping sheet after hardening.

[0085] The amount of the trifunctional or higher curable compound is preferably 0.2 to 20 parts by mass, more preferably 0.3 to 5 parts by mass, and even more preferably 0.8 to 3 parts by mass relative to 100 parts by mass of the thermosetting resin. By making the amount of the trifunctional or higher curable compound 0.2 parts by mass or more, the adhesion between the anti-peeling layer and the substrate can be further improved, thereby further improving the reliability.

[0086] Furthermore, by setting the trifunctional or higher curable compound to 20 parts by mass or less, the anti-flaking sheet 6 can easily follow the shape of the electronic component 2 and deform during heating and pressing in the manufacturing step of the electronic component mounting substrate described later, thereby easily forming a defect-free anti-flaking layer.

[0087] [Lubricant]

[0088] The anti-stripping layer 3 may also contain lubricants such as waxes. By adding these, the smoothness of the anti-stripping layer surface increases, thereby easily improving the wear resistance. Since the surface of the anti-stripping layer is not easy to break, further improvement in reliability can also be expected. For example, as wax, there can be listed: animal and plant waxes such as beeswax, lanolin wax, spermaceti, candelilla wax, carnauba wax, rice bran wax, wood wax, jojoba oil, palm oil; minerals such as montan wax, ozokerite, ceresin, paraffin, microcrystalline wax, and paraffin fat (petrolatum); petroleum wax; synthetic waxes such as Fischer-Tropsch wax, polyethylene wax, oxidized polyethylene wax, oxidized polypropylene wax, montan wax derivatives, paraffin derivatives, microcrystalline wax derivatives, and Teflon (registered trademark) wax.

[0089] 《Padding (B)》

[0090] The anti-stripping layer 3 contains filler (B). By appropriately changing the type, average particle size and addition amount of filler (B), the index Y and the rate of change X of the static friction coefficient can be controlled. In addition, the cohesive force in the anti-stripping layer 3 can be adjusted so that mechanical properties such as the maximum point stress T are within a good range.

[0091] Insulating fillers are used when insulation is required, conductive fillers are used when conductivity is required, and electromagnetic wave absorbing fillers are used when electromagnetic wave absorptivity is required. The shape of the filler can be appropriately selected. For example, flaky, needle-shaped, spherical, dendritic, and fibrous fillers can be listed. Fillers of different shapes can also be used in combination. As a preferred example, a combination of different spherical fillers with an average particle size of more than 10 times or a combination of flaky fillers and dendritic fillers can be listed.

[0092] Examples of the insulating filler include non-metallic inorganic fillers such as silica, alumina, boron nitride, aluminum nitride, magnesium silicon nitride, silicon carbide, titanium dioxide, glass, and ceramics. The insulating filler may be used alone or in combination of two or more.

[0093] Conductive fillers include metal fillers, conductive ceramic fillers, and mixtures thereof. Metal fillers include metal powders such as gold, silver, copper, and nickel, alloy powders such as solder, silver-coated copper powder, gold-coated copper powder, silver-coated nickel powder, and core-shell fillers of gold-coated nickel powder. From the perspective of obtaining excellent conductive properties, conductive fillers containing silver are preferred. From the perspective of cost, silver-coated copper powder is most preferred.

[0094] Examples of electromagnetic wave absorbing fillers include iron, Fe-Ni alloy, Fe-Co alloy, Fe-Cr alloy, Fe-Si alloy, Fe-Al alloy, Fe-Cr-Si alloy, Fe-Cr-Al alloy, Fe-Si-Al alloy and other iron alloys, ferrites such as Mg-Zn ferrite, Mn-Zn ferrite, Mn-Mg ferrite, Cu-Zn ferrite, Mg-Mn-Sr ferrite, Ni-Zn ferrite and carbon fillers, etc. Examples of carbon fillers include fillers containing acetylene black, Ketjen black, furnace black, carbon black, carbon fiber, carbon nanotubes, graphene fillers, graphite fillers and carbon nanowalls.

[0095] The average particle size of the filler (B) is preferably 0.005 μm to 50 μm. From the viewpoint of maintaining the smoothness of the surface of the anti-flaking layer, reducing the influence of wear powder during wear, and improving wear resistance, the average particle size of the filler (B) is more preferably 0.02 μm to 20 μm.

[0096] The content of filler (B) in 100% by mass of the anti-stripping layer is preferably 0.1% by mass to 80% by mass, and more preferably 1.0% by mass to 35% by mass from the viewpoint of improving surface properties and improving scratch resistance while suppressing the fall of filler (B) from the surface of the anti-stripping layer. When the content of filler (B) is 80% by mass or less, wear resistance is further improved.

[0097] BET specific surface area of ​​the filler (B) in the anti-stripping layer [m 2 The product of the specific surface area and the content [mass %] of the filler (B) in 100 mass % of the anti-flaking layer (hereinafter referred to as the product of the specific surface area and the content) is preferably 0.01 to 15, and more preferably 0.1 to 10. When two or more fillers (B) are used, the product of the specific surface area and the content is the sum of the products of the specific surface areas and the contents required for the various fillers (B) contained in the anti-flaking layer.

[0098] If the product of the specific surface area and the content is within the range, the filler (B) acts as a reinforcing material in the anti-stripping sheet, so that in the manufacturing step of the electronic component mounting substrate described later, the anti-stripping sheet 6 can be easily prevented from breaking during heating and pressurization, thereby easily forming a defect-free anti-stripping layer.

[0099] When the product of the specific surface area and the content is 15 or less, the scratch resistance and the peeling resistance can be easily optimized by further ensuring the adhesion between the peeling prevention layer and the substrate and the electronic component.

[0100] BET specific surface area of ​​filler (B) [m 2 / g] is preferably 0.1 to 150.

[0101] The anti-flaking sheet 6 may contain a flexibility adjuster. The flexibility adjuster can easily improve wrinkles or cracks during the molding process of the anti-flaking sheet 6. Examples of the flexibility adjuster include plasticizers and inert thermoplastic resins that are scientifically non-reactive.

[0102] Examples of the plasticizer include fatty acid esters, phthalic acid esters, aromatic polycarboxylic acid esters, and polyesters.

[0103] Examples of the fatty acid ester include trioctyl trimellitate (TOTM), manufactured by Mitsubishi Gas Chemical Trading Co., Ltd., butyl stearate, Unistar M-9676, Unistar M-2222SL, Unistar H-476, Unistar H-476D, Panasate 800B, Panasate 875, Panasate 810 (these are trade names, manufactured by NOF Corporation), DBA, DIBA, DBS, DOA, DINA, DIDA, DOS, BXA, DOZ, and DESU (these are trade names, manufactured by Daihachi Chemical Corporation).

[0104] Examples of the phthalic acid ester include DMP, DEP, DBP, #10, BBP, DOP, DINP, DIDP (these are trade names, manufactured by Daihachi Chemical), PL-200, DOIP (these are trade names, manufactured by CG Ester), and Sansocizer DUP (trade name, manufactured by Shin Nippon Chemical).

[0105] Examples of the aromatic polycarboxylic acid ester include TOTM (trade name, manufactured by Daihachi Chemical Industry Co., Ltd.), Monocizer W-705 (trade name, manufactured by Daihachi Chemical Industry Co., Ltd.), UL-80, and UL-100 (these are trade names, manufactured by ADEKA).

[0106] Examples of the polyester include Polycizer TD-1720, Polycizer S-2002, Polycizer S-2010 (these are trade names, manufactured by DIC), and BAA-15 (trade name, manufactured by Daihachi Chemical).

[0107] Among these, DMP, DEP, DBP, DOP, DINP, DIDP, and TOTM (these are trade names) are more preferable. The plasticizer may be used alone or in combination of two or more.

[0108] Examples of the inert thermoplastic resin include polyolefin resins, vinyl resins, styrene-acrylic resins, diene resins, terpene resins, petroleum resins, cellulose resins, polyamide resins, polyurethane resins, polyester resins, polycarbonate resins, polyimide resins, liquid crystal polymers, and fluororesins. The inert thermoplastic resin is not particularly limited, but from the perspective of heat resistance, more preferably the inert thermoplastic resin is polyamide resin, polyurethane resin, polyester resin, polycarbonate resin, polyimide resin, liquid crystal polymer, and fluororesin.

[0109] Furthermore, in order to improve the adhesion with the substrate 1 and the electronic component 2, the anti-stripping sheet 6 may also contain an adhesion-imparting resin. The so-called adhesion-imparting resin is a component that auxiliary improves the adhesion and has a weight average molecular weight of less than 5,000, which is different from the thermoplastic resin and the adhesive. Examples of the adhesion-imparting resin include rosin-based resins, terpene-based resins, alicyclic petroleum resins, and aromatic petroleum resins.

[0110] The anti-stripping sheet 6 may further include a colorant, an ultraviolet (UV) developer, a flame retardant, a lubricant, an anti-adhesive agent, and the like.

[0111] Examples of the colorant include organic pigments, carbon black, blue ochre, red lead, zinc white, titanium oxide, black lead, and dyes.

[0112] Examples of the UV developer include fluorescent pigments, fluorescent dyes, and fluorescent bodies.

[0113] Examples of the flame retardant include halogen-containing flame retardants, phosphorus-containing flame retardants, nitrogen-containing flame retardants, and inorganic flame retardants.

[0114] Examples of the lubricant include fatty acid esters, hydrocarbon resins, paraffin wax, higher fatty acids, fatty acid amides, aliphatic alcohols, metal soaps, and modified silicones.

[0115] Examples of the anti-blocking agent include calcium carbonate, silicon dioxide, polymethylsilsesquioxane, and aluminum silicate.

[0116] In addition, these additives may be used alone or in combination of two or more.

[0117] 《Thickness of anti-peeling layer A2》

[0118] The thickness A2 of the anti-peeling layer 3 is 5 μm to 300 μm, but is more preferably 15 μm to 200 μm from the viewpoint of achieving both the anti-peeling property (wear resistance, scratch resistance) of the electronic component 2 and thinning. Figure 2As shown, the thickness A2 is a measured value of a certain portion where the thickness is highest and is formed in the upper surface region of the electronic component 2 in the cross-sectional image of the electronic component 2 .

[0119] 《Maximum point stress T of anti-spalling layer》

[0120] The maximum point stress T of the anti-peeling layer 3 is a value obtained by a tensile test according to Japanese Industrial Standards (JIS) K 7162. Specifically, it is the maximum stress T when the anti-peeling layer having an effective tensile size of 20 mm×23 mm is stretched at 50 mm / min under an environment of 100°C (in the atmosphere, 50% RH).

[0121] The maximum point stress T is preferably 1 MPa or more and 100 MPa or less, and more preferably 15 MPa or more and 40 MPa or less.

[0122] When the maximum point stress T is 1 MPa or more, the wear resistance or damage resistance can be further improved. On the other hand, when the maximum point stress T is 100 MPa or less, when the anti-stripping layer is formed on the electronic component, the followability of the anti-stripping sheet 6 to the electronic component 2 is further improved. Furthermore, it is easy to suppress the generation of gaps between the anti-stripping layer 3 and the substrate 1 or between the anti-stripping layer 3 and the electronic component 2, or the peeling of the electronic component 2 or the fracture of the anti-stripping layer 3 at the corner due to the easy generation of cracks or cracks in the anti-stripping layer 3, and other appearance and processing defects.

[0123] The maximum point stress T of the anti-stripping layer 3 can be adjusted, for example, by the selection of thermoplastic resin or thermosetting resin, the crosslinking density in the anti-stripping layer, and the selection of fillers. Regarding the crosslinking density, it is preferred to adjust the functional groups and equivalents of the curable compound in the composition used to form the anti-stripping layer. Regarding the selection of fillers, it can be selected based on factors such as the material or shape, size, surface state, specific surface area, and addition amount of the filler, but it is preferred to consider the specific surface area and addition amount of the filler.

[0124] 《Tg of anti-stripping layer》

[0125] The Tg of the anti-peeling layer 3 is a value measured using a dynamic viscoelasticity measuring device. When the Tg of multiple anti-peeling layers can be confirmed, it is set to represent the highest value of tanδ. The Tg of the anti-peeling layer 3 is preferably above 5°C and below 180°C, and more preferably above 20°C and below 80°C. By making the Tg above 5°C and below 180°C and adjusting the fluidity of the anti-peeling layer, the anti-peeling layer can be easily processed into an optimal shape, so that the index Y can be easily placed in the optimal range. In addition, by making the Tg above 20°C and below 80°C, it is easy to make the resistance to frictional heat caused by wear or thermal damage in the inspection in the later step coexist, thereby further improving reliability.

[0126] When the binder (A) contains a thermosetting resin, the maximum point stress T and Tg refer to the substance after heat curing.

[0127] Anti-peeling sheet

[0128] like Figure 3 As shown, the anti-stripping sheet 6 is a precursor of the anti-stripping layer 3. When the anti-stripping sheet 6 contains a thermosetting resin, the anti-stripping sheet 6 is heated at a time and temperature above a prescribed level to cause a curing reaction to form the anti-stripping layer 3. For surface protection, the anti-stripping sheet 6 may also include a peelable sheet on one or both sides. In addition, a buffer material 7 used in the coating protection step using the anti-stripping sheet 6 described later may also be pre-laminated.

[0129] 《Method for producing anti-stripping sheet》

[0130] The method for producing the anti-stripping sheet 6 is not particularly limited, and examples thereof include a method of applying a composition obtained by dissolving the adhesive (A) or other materials forming the anti-stripping layer 3 in a solvent or the like to a releasable sheet, etc. Examples of the coating method include gravure coating, kiss coating, die coating, lip coating, notch wheel coating, scraper coating, roll coating, knife coating, spray coating, rod coating, spin coating, dip coating, or various printing methods.

[0131] In order to achieve a desired thickness, the anti-flaking sheet 6 in the present disclosure may be laminated with two or more anti-flaking sheets. The laminated structure may be composed of only the anti-flaking sheet or may include a layer having a specific function as an intermediate layer.

[0132] 《Application of anti-peeling sheet》

[0133] The peeling prevention sheet 6 in the present disclosure can be preferably used for protecting various substrates 1, that is, various substrates such as rigid substrates and flexible printed circuit (FPC) substrates, and electronic components 2 mounted thereon.

[0134] In addition, the anti-stripping sheet 6 in the present disclosure shows sufficient adhesion in practice when the substrate 1 is any one of metal, resin, fiber, ceramic, glass and conductive silicone. As metal, aluminum, copper, brass, stainless steel, iron, chromium, etc. can be used. As resin, epoxy resin, polyethylene terephthalate, polyimide, polyamide, polyethylene, polypropylene, polyolefin-based graft polymer, polystyrene, polyvinyl chloride, etc. can be used. In this way, the anti-stripping sheet 6 can also be preferably used for the adhesion between heterogeneous materials with different polarities.

[0135] 《Method for manufacturing a substrate for mounting electronic components》

[0136] A method for manufacturing an electronic component mounting substrate will be described.

[0137] The manufacturing method of the electronic component mounting substrate disclosed in the present invention can be performed by the following steps, namely, a step of mounting one or more electronic components 2 on the substrate 1 (step i), a step of preparing an anti-stripping sheet 6 (step ii), a step of placing the anti-stripping sheet 6 in a manner that the highest electronic component among the electronic components 2 is in contact with the anti-stripping sheet 6 (step iii, also referred to as a temporary stretching step), a step of deforming the anti-stripping sheet 6 along the shape of each electronic component 2 by heating and pressing and covering at least a portion of the electronic component 2 and the substrate 1 (step iv), and a step of hardening the deformed anti-stripping sheet 6 in a deformed state to form an anti-stripping layer 3 (step v), and the electronic component mounting substrate can be covered and protected by the anti-stripping layer 3 formed by the anti-stripping sheet 6 disclosed in the present invention. Furthermore, steps iv and v can also be set as a series of steps.

[0138] In the following, regarding steps iii to v, use Figure 3 An example of a method for covering and protecting an electronic component mounting substrate by heating and pressing using the peeling prevention sheet 6 will be described.

[0139] (Step iii: Anti-peeling sheet placement step)

[0140] A mounting substrate 100 is prepared in which electronic components 2 are mounted on a substrate 1 directly or via solder bumps 4. The electronic components 2 are semiconductor chips, capacitors, transistors, inductors, thermistors, etc., and can be mounted on the substrate 1 via solder bumps 4, and there may be gaps between the electronic components 2 and the substrate 1. In addition, the heights of the electronic components 2 may be different.

[0141] Then, the anti-stripping sheet 6 cut into a predetermined size is placed on the mounting surface of the electronic component 2. The anti-stripping sheet 6 is temporarily attached to a member having the height of the electronic component 2. In addition, the anti-stripping sheet 6 may be bent and contacted with other electronic components 2 (in Figure 3 (not shown in the figure).

[0142] Furthermore, a buffer material 7 may be laminated on the anti-stripping sheet 6. Figure 3 The example using the buffer material 7 is shown. The buffer material 7 may be laminated after the anti-stripping sheet 6 is placed, or a laminated body obtained by laminating the anti-stripping sheet 6 and the buffer material 7 may be placed in advance. The buffer material 7 is a material that softens or melts when heated and pressurized, and has the function of promoting the followability of the anti-stripping sheet 6 to the electronic component 2 and the followability to the gap between the electronic components 2.

[0143] The buffer material 7 is not particularly limited as long as it is a thermoplastic material, but preferably has a melting temperature and a glass transition point (Tg) lower than the temperature during pressurization. Preferred examples of the buffer material 7 include polyolefin films, vinyl chloride films, and polyvinyl alcohol (PVA) films. Although it depends on the depth of the groove, the thickness of the buffer material 7 is generally about 100 μm to 1 mm. In the case of stacking a plurality of buffer materials 7, the total thickness of these is preferably within the above range.

[0144] The electronic component mounting substrate of the present disclosure is an example, and the structures of the electronic component and the substrate are not particularly limited, and there may or may not be a gap between the electronic component 2 and the substrate 1. The arrangement position of the mounted electronic component 2 is not limited.

[0145] (Step iv: step of covering at least a portion of the electronic component and the substrate)

[0146] Then, by applying heat and pressure using the heating and pressing machine 20, the anti-stripping sheet 6 is deformed in a manner that follows the shape of each electronic component 2, that is, in a manner that follows the upper surface and side surface of the electronic component 2, and follows at least a portion of the electronic component group and the substrate 1. The buffer material 7 softens or melts due to heat, and promotes the anti-stripping sheet 6 to follow the unevenness between the electronic components of the mounting substrate 100.

[0147] It is also preferred to sandwich a peelable sheet (not shown) between the heating and pressing machine 20 and the buffer material 7 during heating and pressing. The peelable sheet is a sheet obtained by subjecting a substrate such as paper or plastic to a known peeling treatment. In addition, a plastic sheet with low polarity such as Teflon (registered trademark) can also be used.

[0148] The heating temperature can be any temperature at which the anti-stripping sheet 6 is appropriately softened, deformed along the shape of each electronic component 2, and enters the gaps between each electronic component, preferably 100°C to 260°C, more preferably 120°C to 240°C. If the heating temperature is above 100°C, it is easy to prevent the anti-stripping sheet 6 from decreasing the penetration into the gaps between each electronic component. On the other hand, if the heating temperature is below 260°C, the thermosetting reaction of the thermosetting resin of the anti-stripping sheet 6 proceeds rapidly, thereby easily preventing the anti-stripping sheet from decreasing the penetration into the gaps between the electronic components.

[0149] The pressure during heating and pressing is preferably 0.01 MPa to 15 MPa, and more preferably 0.1 MPa to 6.0 MPa. By heating and pressing at a pressure within the above range, embedding properties can be further improved without damaging the electronic components.

[0150] The heating time is usually 0.5 minutes to 30 minutes, preferably in the range of 1 minute to 20 minutes. If the heating time is 0.5 minutes or more, it is easy to prevent the anti-peeling sheet 6 from penetrating into the electronic components carried thereon from decreasing. On the other hand, if the heating time is 30 minutes or less, it is easy to prevent the following situations: thermal decomposition or oxidation of the thermosetting resin is likely to occur, and the possibility of reduced reliability of the bonding part caused by the reaction product etc. is increased. The heating and pressurizing step is preferably performed in a vacuum state.

[0151] As a method of heating and pressing, in addition to using a heating and pressing machine, a method of laminating metal plates of appropriate weight so as to achieve a predetermined pressure and then placing the laminate into an oven is also preferred.

[0152] On the other hand, as a heating and pressing method other than the heating and pressing machine, a vacuum forming method or a vacuum pressure forming method is also preferable.

[0153] (Step v: Step of hardening the deformed anti-stripping sheet)

[0154] When the anti-stripping sheet 6 includes a thermosetting resin, after heating and pressing, the anti-stripping sheet 6 is deformed and then heated at a temperature of 150° C. to 230° C. for 10 to 60 minutes, thereby thermally curing the thermosetting resin in the anti-stripping sheet 6 to form an anti-stripping layer 3. The anti-stripping layer 3 is firmly attached to the electronic component 2 and the substrate 1, and functions as an anti-stripping layer 3 for preventing and protecting the electronic component 2 from damage due to external impact or scratches. Furthermore, in the stage of (step iv), for example, by setting the temperature of heating and pressing to 150° C. or more and the time to 30 minutes or more, thermal curing can be completed to form the anti-stripping layer 3.

[0155] The electronic component mounting substrate disclosed in the present invention preferably has an anti-stripping layer as the outermost layer. In addition, other functional layers may be laminated on the inner layer side. The so-called other functional layers are, for example, layers having functions such as electrical conductivity, hard coating, water vapor barrier, oxygen barrier, thermal conductivity, low dielectric constant, high dielectric constant, and heat resistance. Among them, the functional layer having electrical conductivity is sometimes used to protect the electronic components to be covered and protected from the influence of electromagnetic wave noise.

[0156] Figure 4 , an example of the structure of an electronic component mounting substrate 12 including a conductive functional layer 8 on an anti-peeling layer 3 is shown. The conductive functional layer 8 is formed on the upper side (upper layer) of the anti-peeling layer 3 on the paper surface and is connected to the ground wire 9. The connection point with the ground wire 9 may exist on the surface of the substrate 1 or on the side of the substrate 1. The conductive functional layer 8 can be formed by forming a metal layer (not shown) on the surface of the anti-peeling layer 3 by sputtering or plating, or by laminating a conductive metal foil or nonwoven fabric on the anti-peeling layer 3.

[0157] Electronic Equipment

[0158] The electronic component mounting substrate disclosed in the present invention is preferably included in electronic devices such as notebook computers, mobile phones, smart phones, and tablet terminals in addition to liquid crystal displays and touch panels.

[0159] Example

[0160] Hereinafter, the present disclosure will be described in detail with reference to Examples and Comparative Examples, but the present disclosure is not limited to the following Examples. In addition, the following "parts" are values ​​based on "parts by mass" unless otherwise specified.

[0161] "raw material"

[0162] The raw materials used in the examples are shown below.

[0163] <Thermosetting resin>

[0164] Thermosetting resin (r1): polyurethane resin (molecular weight (Mw) = 130000, acid value 10 mgKOH / g, Tg = 20°C), manufactured by TOYOCHEM Co., Ltd.

[0165] Thermosetting resin (r2): polyurethane resin (molecular weight (Mw) = 125000, acid value 10 mgKOH / g, Tg = -6°C), manufactured by TOYOCHEM Co., Ltd.

[0166] Thermosetting resin (r3): acrylic resin (molecular weight (Mw) = 55000, acid value 7 mgKOH / g, Tg = -20°C), manufactured by TOYOCHEM Co., Ltd.

[0167] <Curing compound>

[0168] Curable compound (c1): tetrafunctional epoxy resin "TETRAD-X" (epoxy equivalent = 100 / eq), manufactured by Mitsubishi Chemical Corporation

[0169] Curable compound (c2): bifunctional epoxy resin "jER828" (epoxy equivalent = 189 g / eq), manufactured by Mitsubishi Chemical Corporation

[0170] Curable compound (c3): bifunctional epoxy resin "AER9000" (epoxy equivalent = 380 g / eq), manufactured by Asahi Kasei E-materials Co., Ltd.

[0171] <Lubricant>

[0172] Lubricant (L1): Carnauba wax "CERACOL 79" (non-volatile content 20% by mass), manufactured by BYK

[0173] <Padding (B)>

[0174] Filler f1: Carbon black "MA100" (trade name, average primary particle size: 24 nm, BET specific surface area: 120 m 2 / g), manufactured by Mitsubishi Chemical Corporation

[0175] Filler f2: Silica "UltraSil U360" (trade name, average primary particle size: 28 nm, BET specific surface area: 50 m 2 / g) Manufactured by NANOCYL

[0176] Filler f3: Silica "ADMAFINE SO-C5" (trade name, average primary particle size: 2.0 μm, BET specific surface area: 2.1 m 2 / g), manufactured by ADMATECHS

[0177] Filler f4: Plate-shaped boron nitride "HP-1" (trade name, average primary particle size: 9.0 μm, BET specific surface area: 3.1 m 2 / g), manufactured by JFE MINERAL

[0178] Filler f5: silica "EXCELICA SE-30K" (trade name, average primary particle size: 25.1 μm, BET specific surface area: 0.7 m 2 / g) Made by Tokuyama

[0179] Filler f6: flaky silver powder "FA-S-18" (trade name, average primary particle size: 3.1 μm, BET specific surface area: 2.0 m 2 / g), manufactured by Dow (DOWA)

[0180] Filler f7: dendritic silver-coated copper powder "ACAX-225M" (trade name, average primary particle size: 7.4 μm, BET specific surface area: 0.86 m 2 / g), manufactured by Mitsui Mining & Smelting Co., Ltd.

[0181] 《Measurement Method》

[0182] <Change rate X of static friction coefficient during reciprocating wear test>

[0183] For the anti-peeling layer of each embodiment and comparative example, a chip (electronic component) made of molded resin (sealing resin) in the resin-containing area below the anti-peeling layer or a smooth portion of 6 mm×6 mm square or more on the electronic component mounting substrate is used as a test sample for measurement. A continuous weighted surface property measuring instrument, HEIDON TRIBOGEAR, model (TYPE): 22H (manufactured by HEIDON Scientific Co., Ltd.), is used to place the fully dried test sample on the test bench, apply a load of 100 g to the friction part, and record the static friction coefficient μk at the 100th and 300th reciprocating times. 100 , static friction coefficient μk 300 In addition, a ball indenter was used as the measuring fixture when the test sample surface was reciprocated, and a stainless steel (SUS) ball (φ (diameter) 3.0 mm) was used as the friction member. The static friction coefficient μk 100 , static friction coefficient μk 300 The change X in the static friction coefficient during the reciprocating wear test was calculated by applying the following [Equation 1].

[0184] [Formula 1] X = (μk 300 -μk 100 ) / μk 100 ×100

[0185] <Index Y>

[0186] like Figure 2As shown, the anti-peeling layer 3 and the electronic component mounting substrate 12 of each embodiment and comparative example prepared by the method described later are cut in section by a grinding method, and the curvature radius R1 and the curvature radius R2 of the curved surface of the corner of the electronic component and the coated anti-peeling layer are obtained by a digital microscope VHX-7000 (trade name, manufactured by KEYENCE). The thickness of the thinnest part in the corner of the anti-peeling layer (the corner thickness of the anti-peeling layer) A1 is obtained in the same way. In the evaluation of these electronic components and anti-peeling layers, a component with a size of 0.3 mm on the short side and 0.6 mm on the long side of the MLCC is used (hereinafter also referred to as 0603MLCC, 0603MLCC 30). The obtained curvature radius R1, curvature radius R2, and corner thickness A1 of the anti-peeling layer are applied to the following [Formula 2] to calculate the index Y.

[0187] [Formula 2] Y = R2 / (R1+A1)

[0188] <Thickness of anti-peeling layer A2>

[0189] The thickness of the anti-peeling layer in the electronic component mounting substrate is defined as the film thickness of a certain portion of the upper surface region of the electronic component observed by a digital microscope VHX-7000 (trade name, manufactured by KEYENCE) after cross-sectioning by a grinding method. The same measurement is performed on cross-sectioned samples of 5 different electronic component mounting substrates, and the average value is defined as the thickness A2.

[0190] <Average particle size of filler (B)>

[0191] The average particle size of the filler (B) is obtained by averaging 20 primary particles observed in an image magnified by about 50,000 to 1,000,000 times using a transmission electron microscope (TEM). In addition, when the particle shape of the filler (B) has an average aspect ratio (major axis length / minor axis length) of 1.5 or more, the average particle size is obtained by averaging the major axis length.

[0192] <Maximum point stress T of spalling prevention layer>

[0193] The anti-peeling sheet with a peeling film of each embodiment / comparative example is heated at 180°C for 2 hours and cut into a size of 20 mm in width × 60 mm in length. Subsequently, a measurement sample (anti-peeling layer) including an anti-peeling sheet is obtained by peeling off the peeling film. Each measurement sample (anti-peeling layer) is placed in an environment of 100°C (in the atmosphere, 50% RH (relative humidity)) from room temperature (e.g., 25°C). After 1 minute, a tensile test is performed at this temperature using a small desktop testing machine EZ-TEST (trade name, manufactured by Shimadzu Corporation) at a tensile speed of 50 mm / min and a relative humidity of 50%, with an effective tensile size of 20 mm×23 mm. Then, the maximum stress T (maximum point stress T) at a tensile speed of 50 mm / min is obtained.

[0194] <Glass transition temperature Tg>

[0195] For the measurement samples (anti-peeling layer) of each embodiment and comparative example, Tg was measured by a dynamic viscoelasticity measuring device DVA-200 (trade name, manufactured by IT Measurement and Control Co., Ltd.) in accordance with JIS K7198. The measurement sample used was a sample in which the anti-peeling layer of each example was cut into 0.5 cm × 3 cm and the peeling film was peeled off. The deformation method was stretching, and the temperature at which the main dispersion peak of the loss tangent (tanδ) measured at a strain of 0.08%, a frequency of 10 Hz, and a heating rate of 10°C / min appeared was set to Tg. However, for the measurement result in the case where the anti-peeling layer was brittle and broke in the middle of the measurement, Tg could not be calculated, so it was expressed as "unable to measure" in the embodiment table.

[0196] 《Production of anti-peeling sheet》

[0197] [Example 1]

[0198] 100 parts of thermosetting resin r1 (solid content), 2.0 parts of hardener c1, 10 parts of hardener c2, 2.9 parts of filler f1, and 159 parts of filler f4 were placed in a container, and a mixed solvent of toluene:isopropyl alcohol (mass ratio 2:1) was added so that the non-volatile component concentration became 45% by mass, and stirred for 10 minutes by a disperser to obtain a composition. The composition was applied to a release sheet using a scraper in a dry thickness of 80 μm. Then, it was dried at 100° C. for 2 minutes to obtain the anti-stripping sheet of Example 1.

[0199] [Examples 2 to 21, Comparative Examples 1 to 4]

[0200] The same operation was performed except that the types and blending amounts of the materials in Tables 1 to 3 were changed to obtain the anti-flaking sheets (laminated sheets) of Examples 2 to 21 and Comparative Examples 1 to 4. The evaluation results described below are also described for each anti-flaking sheet.

[0201] [Production of electronic component mounting substrate 1]

[0202] (Manufacturing of mounting substrate)

[0203] Prepare a substrate (mounting substrate) on which molded sealed electronic parts (1 cm × 1 cm) are mounted in an array of 5 × 1 and 0603 MLCCs (length 0.6 mm, width 0.3 mm) are mounted in an array of 8 × 2 on a substrate containing epoxy glass. The thickness of the substrate is 0.6 mm, and the molded seal thickness, i.e., the height (part height) H from the upper surface of the substrate to the top surface of the molded seal material, is 0.7 mm. The mounting interval of 0603 MLCC is 200 μm.

[0204] The anti-peeling sheet of each example and comparative example was thermocompressed on the mounting substrate at 2 MPa and 180°C for 5 minutes, and the buffer material was peeled off by hand. Thereafter, the substrate was heated at 180°C for 2 hours to obtain the electronic component mounting substrate of each example and comparative example based on Tables 1 to 3.

[0205] "evaluate"

[0206] [Abrasion resistance]

[0207] For the anti-peeling layer of each embodiment and comparative example, the anti-peeling layer on the electronic parts sealed by mold in the mounting substrate is measured as the test area. Using a continuous weight-added surface property measuring instrument, HEIDON TRIBOGEAR model (TYPE): 22H (trade name, manufactured by HEIDON Scientific Co., Ltd.), a fully dried test sample is mounted on the test bench, a load of 100g is applied to the friction part, and the surface state of the test sample is observed after the number of reciprocations according to the following evaluation criteria. Then, whether the substrate is exposed and the anti-peeling layer is broken is confirmed (reciprocating wear test). In the case where these evaluations are difficult to observe visually, a digital microscope VHX-7000 (trade name, manufactured by KEYENCE) is used to observe the surface state at 20 times. Furthermore, a ball indenter is used as the measuring fixture when reciprocating on the surface of the test sample, and a SUS ball (φ3.0mm) is used as the friction part. In addition, based on the results, the wear resistance is evaluated according to the following criteria.

[0208] (Evaluation Criteria)

[0209] +++: After 500 reciprocating cycles, the electronic components under the anti-peel layer were not exposed. (Extremely good)

[0210] ++: After 400 reciprocating cycles, the electronic components under the anti-peeling layer were not exposed, but after 500 reciprocating cycles, the electronic components under the anti-peeling layer were exposed. (Good)

[0211] +: After 300 reciprocating cycles, the electronic components under the anti-peeling layer were not exposed, but after 400 reciprocating cycles, the electronic components under the anti-peeling layer were exposed. (Practical level)

[0212] NG: When the number of reciprocating times is less than 300 (i.e. after 300 reciprocating times), the electronic components under the anti-peeling layer are exposed. (Defective)

[0213] [Anti-peeling properties]

[0214] like Figure 5 As shown, for the anti-peeling layer 3 on the corner of the 0603MLCC30 in the electronic component 2 on the electronic component mounting substrate made by the method, the end of the thick Ni-SUS plate 13 (a component in which a nickel layer of 2 μm is formed on the surface of a commercially available SUS304 plate of 0.2 mm thickness) is abutted at 45°, and popped out from the side of the corner of the 0603MLCC30 toward the top surface. The above action is repeated 30 times for each part, and the number of electronic components 30 peeled off from the electronic component mounting substrate after the anti-peeling layer 3 on all 16 0603MLCC30 mounted on the electronic component mounting substrate 12 is counted, and the anti-peeling property is evaluated (peeling test). Here, when the 0603MLCC not covered with the anti-peeling layer was subjected to the same test, the parts peeled off in about 10 tests.

[0215] The term "peeling" means a state where there is no contact between the electronic component mounting substrate and the electronic component or between the electronic component mounting substrate and the peeling prevention layer due to peeling or separation compared to before the test.

[0216] (Evaluation Criteria)

[0217] +++: The number of MLCCs that peeled off was 0. (Extremely good)

[0218] ++: The number of MLCCs that peeled off was 1. (Good)

[0219] +: The number of MLCCs peeled off is 2 or 3. (Practical level)

[0220] NG: The number of MLCCs that peeled off is 4 or more. (Defective)

[0221] [Damage resistance]

[0222] A 30 mm × 80 mm Ni-SUS plate (a component in which a nickel layer with a thickness of 2 μm is formed on the surface of a commercially available SUS304 plate with a thickness of 0.2 mm) is prepared. The anti-stripping sheets (25 mm × 70 mm) of the embodiments and comparative examples are heat-pressed at 2 MPa and 180°C for 5 minutes, respectively, and the buffer material is peeled off by hand. Thereafter, the test sample (anti-stripping layer) is obtained by heating at 180°C for 2 hours. For the test sample, a scratch test is performed in accordance with JIS K7317 using a continuous weighted surface property measuring instrument, HEIDON TRIBOGEAR, model (TYPE): 22H (trade name, manufactured by HEIDON Scientific Co., Ltd.), to continuously measure the vertical load of the anti-stripping sheet coated on the substrate at 50 mm / min. A diamond-made (0.25 mmR) scratching needle is used as the scratching needle on the surface of the test sample, and the damage resistance is evaluated according to the following criteria based on the load when the substrate is exposed from the test sample.

[0223] The scratch in the scratch resistance refers to the state in which the anti-peeling layer is peeled off due to rupture or elongation when the anti-peeling layer is scratched by the tip of the scratching jig, thereby exposing the substrate, and is not a needle mark that can easily change the observation result depending on the observer.

[0224] (Evaluation Criteria)

[0225] +++: Vertical load when substrate is exposed ≧350g (excellent)

[0226] ++: 350g>Vertical load when substrate is exposed ≧250g. (Good)

[0227] +: 250g>vertical load ≧200g when substrate is exposed. (practical)

[0228] NG: 200g>vertical load when substrate is exposed. (Poor)

[0229] [reliability]

[0230] Prepare a molded resin substrate (60mm×50mm), and heat-press the anti-peeling sheet (55mm×45mm) of each embodiment and comparative example for 5 minutes at 2MPa and 180°C, and peel off the buffer material by hand. Thereafter, heat at 180°C for 2 hours to obtain a test sample (anti-peeling layer). For the test sample, according to JIS K5600, 25 checkerboards with a spacing of 1mm were made on the anti-peeling layer on the electronic component using a cross-cutting guide, and then the adhesive tape was crimped, and the end of the tape was peeled off at an angle of 45° to perform a cross-cutting test. The adhesive tape used was an adhesive tape manufactured by Nichiban with a width of 18mm.

[0231] The state (cross-cutting residual ratio) of the peeling-preventing layer remaining on the molded resin substrate in the peeling-preventing layer substrate grid was evaluated according to the following criteria.

[0232] (Evaluation Criteria)

[0233] +++: 100 / 100 cross-section survival rate is shown. (Extremely good)

[0234] ++: The cross-section survival rate is 95 to 99 / 100. (Good)

[0235] +: The cross-cutting survival rate is 80 to 94 / 100. (Practical)

[0236] NG: The cross-cutting residual rate is less than 80 / 100. (Poor)

[0237] A sealing sheet was prepared and evaluated in the same manner as in Example 1 except that the contents, thickness Ta, and protective film were changed to those shown in Tables 1 to 3. In addition, an arbitrary crosslinking agent, oligomer, monomer, polymerization initiator, and other components were also added simultaneously.

[0238]

[0239]

[0240]

[0241] It was confirmed that the anti-peeling layer with a change rate X of the static friction coefficient of less than -50% or more than 200% had problems with wear resistance and anti-peeling as shown in Comparative Example 1 or Comparative Example 2. It was confirmed that the anti-peeling layer with an index Y of less than 0.8 or more than 20.0 had problems with anti-peeling as shown in Comparative Example 3 or Comparative Example 4. In contrast, it was confirmed that the anti-peeling layer of this embodiment, which satisfied all of (1) and (2) of the first invention, also had excellent wear resistance, anti-peeling, damage resistance, and reliability.

[0242] This application claims the priority based on Japanese patent application No. 2023-202349 filed on November 30, 2023, and all the contents disclosed in that application are incorporated into this application.

[0243] Explanation of symbols

[0244] 1: Substrate

[0245] 2: Electronic parts

[0246] 3: Anti-peeling layer

[0247] 4: Solder Bumps

[0248] 5: Hollow part

[0249] 6: Anti-peeling sheet

[0250] 7: Buffer material

[0251] 8: Functional layer

[0252] 9: Ground wire

[0253] 10: Electronic parts mounting substrate

[0254] 11: Electronic parts mounting substrate

[0255] 12: Electronic component mounting substrate with functional layer

[0256] 13: Ni-SUS plate

[0257] 20: Heating and pressing machine

[0258] 30:0603MLCC

[0259] 100: Install the base plate

Claims

1. An electronic component mounting substrate, characterized in that include: substrate; An electronic component mounted on at least one surface of the substrate; as well as The anti-peeling layer covers the substrate and the electronic components. The anti-peeling layer satisfies all of the following (1) and (2). (1) The rate of change X of the static friction coefficient obtained by the following [Formula 1] is not less than -50% and not more than 200%. X = (μk 300 - μk 100 ) / μk 100 × 100 [Equation 1] (μk 100 ; The static friction coefficient of the anti-stripping layer at the 100th reciprocating wear test, μk 300 ; The static friction coefficient of the anti-stripping layer during the 300th reciprocating wear test) (2) The index Y obtained by the following [Formula 2] is 0.8 or more and 20.0 or less. Y=R2 / (R1+A1)[Formula 2] (R1: the curvature radius of the curved surface at the corner of the electronic component in the cross section of the electronic component mounting substrate, R2: the curvature radius of the corner of the anti-peeling layer in the cross section of the electronic component mounting substrate, A1: the thickness of the corner of the anti-peeling layer in the cross section of the electronic component mounting substrate) 2. The electronic component mounting substrate according to claim 1, wherein: The anti-stripping layer comprises an adhesive (A) and a filler (B), The BET specific surface area of ​​the filler (B) [m 2 The product of the content [mass %] of the filler (B) in 100 mass % of the spalling prevention layer is 0.01 to 15 [mass %·m 2 / g].

3. The electronic component mounting substrate according to claim 1 or 2, wherein: The thickness A2 of the anti-stripping layer is 5 to 300 μm. 4 . An electronic device having the electronic component mounting substrate according to claim 1 mounted thereon.

Citation Information

Patent Citations

  • Electronic circuit package using composite magnetic sealing material

    CN107424961A

  • Flexible printed board and manufacturing method of the same

    JP2013074166A

  • Sealing film, sealing method for electronic component mounted substrate, and electronic component mounted substrate coated with sealing film

    WO2018008657A1

  • Electronic component and method for manufacturing same

    WO2021153335A1